Revisiting the Environmental Kuznets Curve: The spatial interaction between economy and territory - Enrico Maria Mosconi; Andrea Colantoni; Filippo Gambella; Eva Cudlínová; Luca Salvati; Jesús Rodrigo Comino (Economies, 2020)
A complex interplay of socio-ecological drivers of change exists at the different spatiotemporal scales affecting environmental degradation. This is a key issue worldwide and needs to be understood to develop efficient management solutions. One of the most applied theories in the regional analysis is the U-shaped relationship between environmental degradation and the level of income in a given economic system or Environmental Kuznets Curve (EKC). Specifically, the EKC hypothesis underlines the (potentially positive) role of formal responses to environmental degradation grounded on government policies that are usually more ambitious in wealthier economic systems. However, there is a lack of knowledge on the role of space in EKC, arguing that spatial variability in the environment-income relationship may indicate additional targets for integrated socio-environmental policies. We hypothesize that a spatially differentiated response to environmental degradation could better adapt to differentiated local contexts. Therefore, to achieve this goal, we present a multi-scale investigation of degradation processes at the local level, providing a refined knowledge of the environment-economy linkages considering more traditional, cross-country and cross-region exercises. Our results demonstrated that-together with temporal, sectoral, and institutional aspects-space and, consequently, the related analysis' spatial scales, are significant dimensions in ecological economics, whose investigation requires improvements in data collection and dedicated statistical approaches.
Keywords: Q05; R10; R14; 330; space; scale; land degradation; externalities; indicators; Italy